Achievements of EU funded project BFIRST on BIPV technology - Machado, Maider; Roman, Eduardo; Vega de Seoane, Jose M.; Esteban, José Carlos; Puig, J. M.; Pellegrino, Michele; Mathas, E.; Charalampopoulos, Andreas; Kalogirou, Soteris A.; Pierret, Stéphane; Reijenga, Tjerk (My University, 2017)
EU funded “Building-integrated fibre reinforced solar technology” (BFIRST) project (Grant Agreement number 296016) was launched in 2012 by a consortium of EU companies, research institutes and universities, led by Tecnalia. The project, which will end in early 2017, is focused on the design, development, fabrication and demonstration of a set of standardized multifunctional photovoltaic products for building integration using an innovative manufacturing solution based on glass fibre-reinforced composite materials. This novel encapsulation technology is the basis for a wide range of new BIPV (building-integrated photovoltaic) products with enhanced building integration possibilities. The resulting modules present advanced characteristics in terms of flexibility of design, adaptability to non-planar geometries, structural properties and lightweight, among others. They provide additional advantages related to cost reduction in transport, manipulation, assembly and installation
Keywords: Photovoltaic products; Fibre-reinforced composite materials